Mr. Lever's address on visit of International Housing Conference to Port Sunlight, 9 August 1907 - Leverhulme, William Hesketh Lever, Viscount, 1851-1925 (1909)
1909 1909 1900s 10 pages xviii. APPENDIX. At 14 years of age: — Height Weight inches. lbs. Higher Grade Schools ... 61.7 94.5 Council Schools (a) ... 58.2 75.8 (b) ... 56.2 75.9 (c) ... 55.2 71.1 Port Sunlight Schools ... 60.7 105 The measurements of Port Sunlight children were taken by Dr. J. Mackenzie, M.B., Ch.B., Resident Medical Officer, Port Sunlight, and he writes as follows: — PORT SUNLIGHT. MESSRS. LEVER BROTHERS LIMITED. I certify that I have taken the weight and height measurements of all the children from five years of age and upwards attending the Port Sunlight Schools. The results are given in the accompanying tabulation (see Appendix). The height measurements were taken with boots off, and the weights in ordinary indoor clothing. (Signed) J. MACKENZIE, M.B., Ch.B. Dr. Arkle comments, in comparing the boys in the Higher Grade Schools and the type (c) Council Schools, that the startling fact is disclosed that a boy of eleven in the Higher Grade School is practically as tall and as heavy as a boy of fourteen in the type (c) Council Schools. We may further add to this that Garden City life at Port Sunlight discloses the fact that the sons and daughters of our artisans and labouring population of Port Sunlight produce superior height and weight at equal ages than are produced in Council Schools in Liverpool at which the children of parents in similar positions are educated. I do not think we need be surprised at this — the development of the child must be affected by the food he eats and by its environment. However that may be, the figures relating to Port Sunlight conclusively prove that, given regularity and permanency of employment to the parents, and consequently also of feeding and clothing of the children, reasonable and proper housing conditions, plenty of surrounding land for healthy open-air recreation, provision of Parks, Swimming Baths, Gymnasia, Football Field, Cricket Field, Clubs, and all that makes for healthy out-door life, and the children of our artisans and labouring people become equal in physique to those of the better classes. Unhappily the statistics relating to type (c) Council Schools equally clearly show that where these conditions do not prevail the effect is disastrous to healthy development during childhood. These statistics of Dr. Arkle, however, only reveal the conditions produced by overcrowding at the commencement of life. Dr. Arkle unfortunately has not been able to take comparative statistics relating to the parents and adults in the classes from whom the children in the various types of schools spring. We can, however, obtain statistics from the Registrar General's return for the United Kingdom, which shows that the death-rate in England varies from about 9 per thousand in suburban areas to about 35 per thousand in congested slum areas, whilst the average death-rate in the United Kingdom is about 16 per thousand. The birth-rate also varies, the average for the United Kingdom being about 26 per thousand. The statistics of death-rate and birth-rate for Port Sunlight are as follows : — STATEMENT SHOWING THE RATIO OF BIRTHS AND DEATHS PER 1,000 OF POPULATION AT PORT SUNLIGHT. Year. Estimated DEATHS BIRTHS Population. per 1,000. per 1,000. 1900 2,007 12.45 48.33 1901 2,331 12.87 51.48 1902 2,484 7.24 39.45 1903 2,580 8.14 52.71 1904 2,610 12.26 47.90 1905 2,700 5.55 42.70 1906 2,900 10.00 35.86 In considering these figures of death-rate of Port Sunlight it is necessary to point out that the death-rate has repeatedly been swelled both with regard to the deaths of children and of old people, by the fact that residents in Port Sunlight often invite their aged and infirm parents and the sick children of their relatives to come and live with them in Port Sunlight. This we know as a fact has often seriously swelled the death-rate. As far as we can ascertain, after making due allowance for the deaths in the Village of non-residents, the death-rate of the inhabitants of Port Sunlight averages about eight to nine per thousand. Another side of Garden City life is revealed by statistics with reference to marriage and the size of families. The following statistics relating to Port Sunlight have been drawn up by Mr. Duncan C. Fraser, the well-known Actuary in Liverpool. Mr. Fraser took for his calculation those employees of Lever Brothers who, at the end of 1905, had seen ten years' service or over with the firm, their age and salary, married, widower or single, and number of children under the age of 17 years. Every employee of ten years' service and over, of the age of 25 or over, was included, from the highest official to the lowest labouring man. On this clear basis Mr. Fraser divided the employees into six grades: — Lower Grade Workmen earning on the average £67 a year. Higher Grade Workmen earning on the average £99 a year. Lower Grade Clerks with an average income of £128 a year. Higher Grade Clerks being the higher section of the clerical staff, Heads of Departments, and men in positions of responsibility, the average earnings being £191 a year. Lower Grade Business Men who were actually engaged in selling the products of the firm, the average income being £346. Higher Grade Business Men who were Directors, Managers and Controllers, with salaries of over £1,000 a year. The above six grades therefore fall into three well marked social divisions — Workingmen, Clerks, and Business Men — and each division is sub-divided into lower and higher grades. To these figures may be added:— 1907. Population 3,412; deaths per 1,000, 7.62: births per 1,000, 31.36. 1908. Population 3,492; deaths per 1,000,10.59; births per 1,000, 33.50. The poputation was ascertained at the end of 1907 by a voluntary census. - July, 1909 36/H24/20